THE MIMETIC CRITICISM IN CHARLES DICKENS’ DAVID COPPERFIELD AND CHINUA ACHEBE’S THINGS FALL APART - M Supriyatno (Diglossia: Jurnal Kajian Ilmiah Kebahasaan dan Kesusastraan, 2012)
Supriyatno Universitas Islam Darul ‘Ulum (UNISDA) Lamongan mizazuhadizavala@yahoo.com  Abstrak Kritik mimesis digunakan untuk menghubungkan imitasi, refleksi, dan representasi kehidupan manusia terhadap karya sastra. Charles Dickens dan Achebe merupakan penulis novel handal yang juga sangat peduli terhadap masalah sosial dalam kehidupan manusia. David Copperfield sebagai salah satu karya Dickens, menangkap fenomena sosial di London selama Revolusi Industri. Sementara itu, Achebe dengan Things Fall Apart nya menangkap kehidupan sengsara dari Igbo masyarakat dalam mempertahankan keyakinan mereka. Artikel ini bertujuan menyelidiki kritik mimesis dari David Copperfield dan Things Fall Apart berkaitan dengan cara penulis dalam menentukan karakter, penokohan, dan karakter utama dari kedua novel. kata kunci: kritik mimesis (mimetic criticism), refleksi (reflection), masalah social (social problem)   Abstract Mimetic Criticism is used to connect the mimetic imitation, reflection, and the representation of human life to literature. Charles Dickens and Achebe is a novelist who is also a reliable very concerned about social issues in human life. David Copperfield is one of the works of Dickens. This novel reveals the social phenomena captured in London during the Industrial Revolution. Meanwhile, Things Fall Apart by Chinua Achebe captured his miserable life of the Igbo people in defending their beliefs. This article aims to investigate the mimetic criticism of David Copperfield and Things Fall Apart deals with the way the author in determining the characters, characterizations, and the main characters of the novel. key words: mimetic criticism, reflection, social problems